2020
DOI: 10.21203/rs.3.rs-26732/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Association between dietary total antioxidant capacity with the risk of helicobacter pylori infection among adult: a case–control study

Abstract: Objective Dietary total antioxidant capacity (TAC) has been assumed as a useful tool to assess the relationship between the cumulative antioxidant food capacity and several chronic disorders. The aim of this study was to evaluate the association between DTAC and risk of Helicobacter pylori in a case-control study. Methods This case-control study was carried out among 150 patients with Helicobacter pylori and 302 healthy subjects aged 18–55 years. Dietary data were collected using a validated 168- items quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Recently, some researchers have established that H. pylori infection is related to the frequency of acne rosacea, therefore its logical to assume that similar treatment for H. pylori disease can be used as a healing method to cure acne rosacea (Yang,2018). (Sohouli et al, 2020) have confirmed in their study that patients with H. pylori infection can increase risk of cancer such as; lymphoma, pancreas disease and atherosclerosis. (Ari et al, 2019) have shown in their study to isolates H. pylori from cholecystectomy samples found it in 40% of patients without gallstones and 20% of those with gallstones, The previous information revealed that H. pylori infection may worsen serum lipid levels through continuing chronic inflammation (Iwai et al, 2019).…”
Section: Introductionmentioning
confidence: 77%
“…Recently, some researchers have established that H. pylori infection is related to the frequency of acne rosacea, therefore its logical to assume that similar treatment for H. pylori disease can be used as a healing method to cure acne rosacea (Yang,2018). (Sohouli et al, 2020) have confirmed in their study that patients with H. pylori infection can increase risk of cancer such as; lymphoma, pancreas disease and atherosclerosis. (Ari et al, 2019) have shown in their study to isolates H. pylori from cholecystectomy samples found it in 40% of patients without gallstones and 20% of those with gallstones, The previous information revealed that H. pylori infection may worsen serum lipid levels through continuing chronic inflammation (Iwai et al, 2019).…”
Section: Introductionmentioning
confidence: 77%